Jahreszahlen der Erdgeschichte - Lotze, Reinhold, 1887-1951 (Salt Lake City, UT : Project Gutenberg, 2022)
"Jahreszahlen der Erdgeschichte" by Reinhold Lotze is a scientific publication written in the early 20th century. This work focuses on the geological history of Earth, emphasizing the concept of geological time measurement and the principles behind it. Lotze explores various methods used to date geological events, providing insights into the processes that shaped the Earth over millions of years. The opening of the text introduces the connection between history and geology as disciplines striving to chronicle the events that have shaped the Earth and its inhabitants. Lotze explains the limitations of historical records, which often rely on written documentation, leading to the necessity of using geological evidence to comprehend the Earth's past. He details the transitions from one epoch to another and introduces methodologies for determining the age of geological formations, setting the stage for discussions about the relative and absolute dating of geological events. This scientific approach promises to unravel the vast time scales involved in Earth's history, making for a compelling exploration for anyone interested in geology and the natural sciences. (This is an automatically generated summary.)
Release date is 2022-06-07
Franz L Kuhlmann and the Online Distributed Proofreading Team at https://www.pgdp.net
Keywords: Earth (Planet) -- Age